Sulla libertà di manifestare le proprie opinioni religiose nel luogo di lavoro: brevi note in merito ai casi Achbita e Bougnaoui (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premessa - 2. La pregiudiziale belga: causa C-157/15, G4S Secure Solution - 3. La pregiudiziale francese: causa C-188/15, Bougnaoui e ADDH - 4. Le pronunce “gemelle” della Grande Sezione della Corte di giustizia: la sentenza 14 marzo 2017, Achbita, EU:C:2017:203 e la sentenza 14 marzo 2017, Bougnaoui, EU:C:2017:204 - 5. Uno sguardo alla più recente dottrina ecclesiasticistica - 6. La giurisprudenza della Corte Edu: la sentenza Eweida e altri c. Regno Unito del 15 gennaio 2013 (ricorsi nn. 48420/10, 59842/10, 51671/10 e 36516/10) - 7. Osservazioni conclusive.Freedom to express religious beliefs in the workplace: brief notes on the Achbita and Bougnaoui casesABSTRACT: This paper seek to address the delicate issue of religious freedom, from a juridical perspective, analyzing the Achbita and Bougnaoui cases and comparing it with the Eweida one. It intends to elaborate some of the key question of the doctrinal debate on the links between the expression of one's religious beliefs and the workplace. Can neutrality be a valid defense against discriminations? To what extent can the religious freedom of the worker be sacrificed in favor of the business freedom? These are just some of the questions that are posed to the interpreter and to the scholar of ecclesiastical law. They require a careful evaluation of the values involved and the search for solutions of high balance and responsibility.